Proceedings of the 10th ACM Conference on Web Science 2018
DOI: 10.1145/3201064.3201088
|View full text |Cite
|
Sign up to set email alerts
|

And Now for Something Completely Different

Abstract: Novelty is a key ingredient of innovation but quantifying it is difficult. This is especially true for visual work like graphic design. Using designs shared on an online social network of professional digital designers, we measure visual novelty using statistical learning methods to compare an image's features with those of images that have been created before. We then relate social network position to the novelty of the designer's images. We find that on this professional platform, users with dense local netw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The past research has highlighted a few different facets of the benefits of peer designer influence: better understanding of the design problem, better design outcome, a voluntary support system, and increased novelty of the final product (e.g., Kim and Lee, 2010;Franke et al, 2008;Wachs et al, 2018). To build on the list, the current study suggests peer designer influence as a catalyst for novel product development.…”
Section: Peers' Influence As a Catalyst For Noveltymentioning
confidence: 95%
See 1 more Smart Citation
“…The past research has highlighted a few different facets of the benefits of peer designer influence: better understanding of the design problem, better design outcome, a voluntary support system, and increased novelty of the final product (e.g., Kim and Lee, 2010;Franke et al, 2008;Wachs et al, 2018). To build on the list, the current study suggests peer designer influence as a catalyst for novel product development.…”
Section: Peers' Influence As a Catalyst For Noveltymentioning
confidence: 95%
“…Among different stakeholders, peer designers outside of the immediate design team have been noted to have a major impact on design outcomes. A recent study showed that graphic designers with more cohesive local online networks of peers produced more novel images (Wachs et al, 2018). Furthermore, incorporating peer feedback and support can help novice designers grasp and make sense of design problems (Kim and Lee, 2010).…”
Section: Introductionmentioning
confidence: 99%